add -1 1/3 + (-4 2/3) .

1 answer

To add \(-1 \frac{1}{3}\) and \(-4 \frac{2}{3}\), we first convert the mixed numbers into improper fractions.

  1. Convert \(-1 \frac{1}{3}\): \[ -1 \frac{1}{3} = -\left(1 \times 3 + 1\right) / 3 = -\frac{4}{3} \]

  2. Convert \(-4 \frac{2}{3}\): \[ -4 \frac{2}{3} = -\left(4 \times 3 + 2\right) / 3 = -\frac{14}{3} \]

Now, we can add the two fractions: \[ -\frac{4}{3} + (-\frac{14}{3}) = -\frac{4 + 14}{3} = -\frac{18}{3} = -6 \]

Thus, \(-1 \frac{1}{3} + (-4 \frac{2}{3}) = -6\).